The Influence of Fear of Missing Out On Self-Concept Among High School Students - Wijaya, Lydia Suliyanto; Subroto, Untung (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Social media has now become an integral part of society. However, its usage also carries detrimental effects, including the fear of missing out (FoMO). FoMO is the apprehension of being uninformed about an event and can affect individuals of various ages, including high school students. During adolescence, individuals generally develop multiple aspects of their identity, including self-concept. This study was conducted to determine the extent of FoMO's influence on the self-concept of high school students. A non-experimental quantitative method was used. The instruments used were the Fear of Missing Out Scale and the Personal Self-Concept Questionnaire. The study subjects consisted of 1,114 high school students in Jakarta who had been using social media for at least the past three months. The findings revealed that 18,2% of participants had a low level of FoMO, 66,5% moderate, and 15,3% high. Regarding self-concept, 11,5% of participants scored low, 87% moderate, and 1,5% high. The hypothesis that FoMO affects self-concept was supported, with an effect size of 31.3% and the regression equation Y = 60,461 – 0,348X. This equation implies that a 1% increase in FoMO leads to a 0.348 decrease in self-concept. Conversely, in the absence of an increase in FoMO, the self-concept score is 60.461. The study also found differences in FoMO based on gender, duration of social media use, and residence, with no differences observed based on age and the number of social media platforms used. Differences in self-concept were noted based on gender and duration of social media use.